Governance and the reversal of women's rights: The case of abortion in El Salvador - Jocelyn Viterna; Jose Santos Guardado Bautista; Silvia Ivette Juarez Barrios; Alba Evelyn Cortez (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
States' governance of gender is not unidirectional. In addition to 'stagnation' and 'progress', there can be an active reversal of rights already granted to women. Using the case of abortion rights in El Salvador, this paper investigates the following questions: What are the likely causes of rights reversals? How might rights reversals be more consequential for women's lives than rights stagnations? And how might studying rights reversals as separate and distinct phenomena improve our scholarly understanding of the relationship between gender and development more broadly? Examining the full range of possible transformations in state governance (reversals, stagnations, and progress), we conclude, results in improved theory and more effective interventions.
Keywords: I18; K38; N36; N46; 330; abortion; women; crime; governance; rights; El Salvador